Epidemiology of Primary Multidrug-Resistant Tuberculosis, Vladimir Region, Russia - Ershova, Julia V.; Volchenkov, Grigory V.; Kaminski, Dorothy A.; Somova, Tatiana R.; Kuznetsova, Tatiana A.; Kaunetis, Natalia V.; Cegielski, J. Peter; Kurbatova, Ekaterina V. (Emerging infectious diseases, 2015)
We studied the epidemiology of drug-resistant tuberculosis (TB) in Vladimir Region, Russia, in 2012. Most cases of multidrug-resistant TB (MDR TB) were caused by transmission of drug-resistant strains, and >33% were in patients referred for testing after mass radiographic screening. Early diagnosis of drug resistance is essential for preventing transmission of MDR TB.